2022
DOI: 10.1136/tobaccocontrol-2021-056540
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of tobacco control in sub-Saharan Africa

Abstract: Yearly, tobacco use kills about 8 million people globally, 80% of whom live in low/middle-income countries. Given sub-Saharan Africa’s (SSA) rapidly increasing and youthful population, growing incomes and the increased presence of the tobacco industry, the number of tobacco users is growing. The region is predicted to face a heavier burden of tobacco-related diseases and deaths in the future. We examined the policy, advocacy, economic and media landscapes of tobacco control as well as tobacco industry interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…African markets of tobacco are often unregulated, and tobacco consumption laws are weak or when strong, not fully implemented and enforced (Vellios et al, 2018). Only Madagascar's and Mauritius' tax shares are above the recommended level in Africa (Egbe et al, 2022). In countries such as Malawi, Zimbabwe and Mozambique for example, tobacco leaf production is still high, export value exceeded 1% of GDP (WHO, 2021); and due to limited resources that are allocated to healthcare and the poor health infrastructure (WHO, 2013), the cigarettes smoked effects can only be devastating health.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…African markets of tobacco are often unregulated, and tobacco consumption laws are weak or when strong, not fully implemented and enforced (Vellios et al, 2018). Only Madagascar's and Mauritius' tax shares are above the recommended level in Africa (Egbe et al, 2022). In countries such as Malawi, Zimbabwe and Mozambique for example, tobacco leaf production is still high, export value exceeded 1% of GDP (WHO, 2021); and due to limited resources that are allocated to healthcare and the poor health infrastructure (WHO, 2013), the cigarettes smoked effects can only be devastating health.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…The tobacco industry uses media to manipulate public opinion about tobacco control and to garner the support of people who oppose government’s “intrusion” in their business [ 35 ]. Media as a tool for interference and promotion may be an important tool for the future of public health as it has become a viable tool both for the promotion and discounting of public health [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The African region (WHO AFRO) remains a worthwhile investment destination and lucrative market for the tobacco industry due to the rapidly increasing young population, increased presence of the tobacco industry, increased incomes, lack and weak tobacco control laws, as well as limited local evidence on tobacco use and its impact 18 . It has been shown that tobacco consumption is driven by economic growth 42 .…”
Section: Biological Plausibility and Public Health Implicationsmentioning
confidence: 99%
“…Additional factors render an Africa specific investigation of tobacco and ESCC risk necessary, including that smokeless tobacco use is often concentrated in women and starts at older ages, thus the latency period for cancer development might not be sufficient for the development of cancer before death. Smoking intensity also tends to be low in general, with the African region having the lowest smoking prevalence among all WHO regions 18 …”
Section: Introductionmentioning
confidence: 99%